Yacon, a Potential Tuberous Crop for Florida - Sergio Laredo; Jianjun Chen; Guodong Liu (EDIS)
The purpose of this article is to introduce yacon as a potential crop to Florida growers and the Extension community by providing information on its propagation, production, and utilization as well as nutritional value. It is anticipated that the availability of such information will support the establishment of yacon as a higher-value crop and promote yacon production and utilization in Florida. Written by Sergio Marcelo Gutierrez Laredo, Jianjun Chen, and Guodong Liu, and published by the UF/IFAS Horticultural Sciences Department; 5 pp. https://edis.ifas.ufl.edu/hs1435